Combination of microbiome analysis and serodiagnostics to assess the risk of pathogen transmission by ticks to humans and animals in central Germany - Yvonne Regier; Kassandra Komma; Markus Weigel; Peter Kraiczy; Arttu Laisi; Arto T. Pulliainen; Torsten Hain; Volkhard A. J. Kempf (BMC, 2022)
BackgroundArthropod-borne diseases remain a major health-threat for humans and animals worldwide. To estimate the distribution of pathogenic agents and especially Bartonella spp., we conducted tick microbiome analysis and determination of the infection status of wild animals, pets and pet owners in the state of Hesse, Germany.ResultsIn total, 189 engorged ticks collected from 163 animals were tested. Selected ticks were analyzed by next generation sequencing (NGS) and confirmatory PCRs, blood specimens of 48 wild animals were analyzed by PCR to confirm pathogen presence and sera of 54 dogs, one cat and 11 dog owners were analyzed by serology. Bartonella spp. were detected in 9.5% of all ticks and in the blood of 17 roe deer. Further data reveal the presence of the human and animal pathogenic species of genera in the family Spirochaetaceae (including Borrelia miyamotoi and Borrelia garinii), Bartonella spp. (mainly Bartonella schoenbuchensis), Rickettsia helvetica, Francisella tularensis and Anaplasma phagocytophilum in ticks. Co-infections with species of several genera were detected in nine ticks. One dog and five dog owners were seropositive for anti-Bartonella henselae-antibodies and one dog had antibodies against Rickettsia conorii.ConclusionsThis study provides a snapshot of pathogens circulating in ticks in central Germany. A broad range of tick-borne pathogens are present in ticks, and especially in wild animals, with possible implications for animal and human health. However, a low incidence of Bartonella spp., especially Bartonella henselae, was detected. The high number of various detected pathogens suggests that ticks might serve as an excellent sentinel to detect and monitor zoonotic human pathogens.